2003
DOI: 10.4993/acrt1992.11.201
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Postoperative Adjuvant Oral Immunochemotherapy in Patients With Dukes' B Colorectal Cancer

Abstract: Among 370 patients who underwent radical resection of primary colorectal cancer over a 17-year period, 167 had stage II-Dukes' B cancer. After excluding 10 patients treated with intravenous drugs other than 5-FU or hepatic arterial injection and 11 patients with rare histological types other than typical differentiated adenocarcinoma, the remaining 146 patients were used to assess the utility of Japanese-style oral postoperative adjuvant immunochemotherapy. Ninety-one patients who received oral chemotherapy wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…this would also reduce the mental burden on patients in the low-risk group and aid in the planning of appropriate follow-up. In patients with stage IIIA/IIIa cancer categorized as t1/2n1 (≤3 nodes), tumor cells may be almost completely eliminated by adjuvant chemotherapy and host antitumor immunity, although single cells or small clusters may continue to circulate in the body (14)(15)(16)(17). It has been reported that a true survival benefit is achieved when there is improvement of survival after recurrence (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…this would also reduce the mental burden on patients in the low-risk group and aid in the planning of appropriate follow-up. In patients with stage IIIA/IIIa cancer categorized as t1/2n1 (≤3 nodes), tumor cells may be almost completely eliminated by adjuvant chemotherapy and host antitumor immunity, although single cells or small clusters may continue to circulate in the body (14)(15)(16)(17). It has been reported that a true survival benefit is achieved when there is improvement of survival after recurrence (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…In general, stage I patients received surgery and follow-up without postoperative adjuvant therapy (2,3,10), while stage II patients received postoperative adjuvant chemotherapy with oral UFt/psK for 12 months or longer (11)(12)(13). stage III patients received intravenous 5-FU/lV or 5-FU/lV in combination with cpt-11 for 6 months after surgery, and then received oral UFt/Uzel or UFt/ psK for 12 months or longer (14)(15)(16)(17). In principle, surgical resection was chosen as the first-line treatment for postoperative recurrence/metastasis.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is certain that, as in the case of gastric cancer and large bowel cancer, some viable cancer cells including circulating ONCs escape from the primary tumor and are disseminated throughout the body (11,15,17). These malignant cells are generally destroyed after invading peripheral lymphatics or vessels because they are recognized as foreign and phagocytized by host immune cells (20)(21)(22). However, a very small number of cancer cells that escape from the host defenses may reach distant organs such as the liver or lungs and survive there, although the detailed mechanisms involved remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In general, Stage II patients received postoperative adjuvant chemotherapy with oral UFT/PSK (Krestin) for 12 months or longer (8)(9)(10). Stage III patients received intravenous 5FU/LV or 5FU/LV in combination with CPT-11 for 6 months after surgery, and then received oral UFT/Uzel (an oral calcium folinate) or UFT/PSK for 12 months or longer (11)(12)(13).…”
Section: Methodsmentioning
confidence: 99%